2014
DOI: 10.1073/pnas.1411705111
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ10 determines the expression of the apical Na-Cl cotransporter (NCC) in the early distal convoluted tubule (DCT1)

Abstract: The renal phenotype induced by loss-of-function mutations of inwardly rectifying potassium channel (Kir), Kcnj10 (Kir4.1), includes salt wasting, hypomagnesemia, metabolic alkalosis and hypokalemia. However, the mechanism by which Kir.4.1 mutations cause the tubulopathy is not completely understood. Here we demonstrate that Kcnj10 is a main contributor to the basolateral K conductance in the early distal convoluted tubule (DCT1) and determines the expression of the apical Na-Cl cotransporter (NCC) in the DCT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
173
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(188 citation statements)
references
References 46 publications
(43 reference statements)
13
173
1
1
Order By: Relevance
“…Moreover, immunostaining image demonstrates that cav-1 is highly expressed in the basolateral (Figure 1, F-H), which is identified by positive immunostaining of parvalbumin, a Ca 2+ -binding protein exclusively expressed in the DCT. 21 Because previous study showed that Kir4.1 was expressed in the basolateral membrane of DCT, 13 it is reasonable to assume that Kir4.1 and cav-1 are colocalized in the basolateral membrane of DCT cells. Our previous study demonstrated that c-Src phosphorylated Kcnj10 and that the inhibition of src-family protein tyrosine kinase (SFK), a family of c-Src-like tyrosine kinase, 22 decreased the basolateral 40 pS K + channel activity in DCT1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, immunostaining image demonstrates that cav-1 is highly expressed in the basolateral (Figure 1, F-H), which is identified by positive immunostaining of parvalbumin, a Ca 2+ -binding protein exclusively expressed in the DCT. 21 Because previous study showed that Kir4.1 was expressed in the basolateral membrane of DCT, 13 it is reasonable to assume that Kir4.1 and cav-1 are colocalized in the basolateral membrane of DCT cells. Our previous study demonstrated that c-Src phosphorylated Kcnj10 and that the inhibition of src-family protein tyrosine kinase (SFK), a family of c-Src-like tyrosine kinase, 22 decreased the basolateral 40 pS K + channel activity in DCT1.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed previously, the DCT1 cells have no apical K + channel, and they have a lack of coupling with neighboring cells. 9,13 Therefore, the whole-cell K currents were equal to the basolateral K + conductance. Figure 6A is a set of whole-cell recording showing that K + currents of DCT1 in cav-1 KO mice (513672 pA) were significantly lower than those in WT mice (1,3006205 pA) (n=8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cette hypothèse a été vérifiée chez la souris Kir4.1 -/-. Ces animaux présentent en effet une diminution de l'expression de SPAK et de NCC [30]. Ces résultats permettent d'expliquer comment des mutations inactivatrices du gène codant Kir4.1 peuvent être à l'origine du syndrome EAST (epilepsy, ataxia, sensorineural deafness, and tubulopathy)/SeSAME (seizures, sensorineural deafness, ataxia, mental retardation, and electrolyte imbalance), un syndrome qui touche de nombreux organes et dont les manifestations rénales sont semblables à celles observées chez les patients atteints du syndrome de Gitelman causé, lui, par des mutations inactivatrices de NCC [31,32].…”
Section: Dct -éTat De Baseunclassified